Evaluation of a group antenatal care intervention in two Northern Nigerian states: Quasi-experimental study - William Douglas Evans; Jeffrey Bartlett Bingenheimer; Taiseer Zaman; Chinwe Lucia Ochu; Samson Babatunde Adebayo; Fasiku Adekunle David; Sani Ali Gar; Masduk Abdulkarim (PLoS ONE, 2025)
Background In low- and middle-income countries (LMIC), group antenatal care (gANC) has the potential to reshape the traditional antenatal care (ANC) service delivery model, enhancing the care experience for both women and providers. ANC non-utilization rates are high in some parts of Nigeria, the evidence-based gANC program offers a structured yet flexible model that may increase maternal and child healthcare utilization which may in turn improve outcomes. Methods This is a longitudinal study of women who participated in the gANC program at healthcare facilities sampled in Kaduna and Kano states, Nigeria. We plan to follow this longitudinal cohort over 3 time points of 18 months and to use data on participation in the gANC program as an independent variable to predict program outcomes using multivariate analysis and propensity matching techniques. This is aimed at isolating the causal effect of the number of gANC meetings attended during the index pregnancy on the probability of delivering that pregnancy in a health facility. To achieve that objective, we used inverse-probability weighting in addition to adjusted multivariate logistic regression models. Results Overall, we found that there was high retention at follow-up, and generally high attendance at follow-up, with higher attendance based on other variables such as prior pregnancy and participants who were employed. We had low participants’ attrition well within power analysis assumptions for the study. In terms of causal inference, there is a strong positive relationship between gANC session attendance and facility delivery, with women who attended five or more gANC sessions being approximately twice as likely to deliver in a health facility as those who attended none or one. Adjustment for a set of socio-demographic and prior pregnancy- and delivery-related variables via inverse probability weighting showed that a positive effect on facility delivery persists, especially at the highest levels of gANC session attendance. Discussion Results of this study tend to confirm the main findings from previous studies of gANC, which found that higher levels of participation resulted in higher facility delivery. This study found that it was both scalable in a diverse set of urban and rural healthcare facilities and engagement with the program among eligible women was high. Future research in the current longitudinal study will evaluate long-term effects of gANC on maternal and child health outcomes such as family planning and vaccination. Conclusion The gANC program at scale in Nigeria produced high levels of participation, and resulted in increased facility birthing utilization that were consistent with previous research. Future research should examine how to optimize program impact and enhance sustainability.